METHACRYLIC COPOLYMER AND PRODUCTION METHOD THEREOF, METHACRYLIC COPOLYMER COMPOSITION AND MOLDED ARTICLE
Patent Information
- Application Number
- JP2021565656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-27
- Filing Date
- 2020-12-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-12-17
AI Technical Summary
【0009】 本発明によれば、透明性が高く、ヘイズが小さく、耐熱性が高く、弾性率が高く、吸水率が低い成形体、光学フィルムを包含するフィルム、積層体を得ることができる。
Smart Images

Figure 0007631227000001 
Figure 0007631227000002 
Figure 0007631227000003
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority based on Japanese Patent Application No. 2019-230162, filed on December 20, 2019, and Japanese Patent Application No. 2020-78639, filed on April 27, 2020, the entire disclosures of which are incorporated herein by reference. The present invention relates to a methacrylic copolymer and a method for producing the same, a methacrylic copolymer composition, a molded article, and a laminate. [Background technology]
[0002] Because of their excellent transparency and low optical distortion, (meth)acrylic resins are widely used as optical components such as lenses, prisms, retardation films, light guide plates, light diffusion films, polarizing plate protective films, etc. In recent years, there has been a demand for improved performance of various components, particularly in terms of heat resistance and elastic modulus.
[0003] Random copolymers of methyl methacrylate and α-methylstyrene have long been known to improve the heat resistance and elastic modulus of (meth)acrylic resins. However, α-methylstyrene does not have the ability to be homopolymerized by radical polymerization under industrial conditions, and has low copolymerizability with other monomers, making it difficult to produce the copolymer. For example, Patent Document 1 discloses a copolymer synthesized by a batch-type bulk polymerization method, but the polymerization time is very long and the productivity is low.
[0004] Patent Document 2 discloses a copolymer produced by an emulsion polymerization method. Compared with batch-type bulk polymerization, the emulsion polymerization method has a high polymerization rate and improves productivity, but it is difficult to completely remove additives such as emulsifiers from the obtained polymer, making it difficult to apply the method to optical components.
[0005] Furthermore, Patent Document 3 discloses a (meth)acrylic resin having a lactone ring structure. Patent Document 4 discloses an acrylic resin having an imide structure. Patent Document 5 discloses a (meth)acrylic resin having a maleimide unit. Patent Document 6 discloses a methacrylic resin having an aromatic vinyl monomer unit. All of these improve heat resistance, but there is room for further study on a method for achieving a higher level of balance between heat resistance, high elastic modulus, and low water absorbency. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] US Patent 3135723 [Patent Document 2] Special Publication No. 43-26187 [Patent Document 3] WO2006 / 112207 A1 [Patent Document 4] WO2005 / 108438 A1 [Patent Document 5] JP 2013-033237 A [Patent Document 6] WO2014 / 021264 A1 Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the above circumstances, an object of the present invention is to provide a methacrylic copolymer having high transparency, low haze, high heat resistance, high elastic modulus and low water absorption, a production method thereof, a methacrylic copolymer composition, a molded article and a laminate. [Means for solving the problem]
[0008] As a result of investigations conducted in order to achieve the above object, the present invention has been completed, which includes the following aspects. [1] A methacrylic copolymer comprising 40-87% by mass of methyl methacrylate units, 6-30% by mass of structural units (R) having at least one ring structure in the main chain selected from the group consisting of lactone ring units, glutaric anhydride units, and N-substituted or unsubstituted glutarimide units, and 7-30% by mass of α-methylstyrene units. [2] The methacrylic copolymer according to [1], wherein the structural unit (R) is an N-substituted or unsubstituted glutarimide unit represented by formula (1). [ka] (In formula (1), R 1 are each independently a hydrogen atom or a methyl group, R 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [3] The methacrylic copolymer according to any one of [1] and [2], having a glass transition temperature of 130°C or higher. [4] The methacrylic copolymer according to any one of [1] to [3], which has a saturated water absorption of 2.5% or less. [5] A methacrylic copolymer composition comprising the copolymer according to any one of [1] to [4]. [6] The methacrylic copolymer composition according to [5], further comprising at least one selected from the group consisting of antioxidants and ultraviolet absorbers. [7] The methacrylic copolymer composition according to [5], comprising 51 to 99 mass% of a methacrylic copolymer (A) containing 40 to 87 mass% of methyl methacrylate units, 6 to 30 mass% of structural units (R) having at least one ring structure selected from the group consisting of lactone ring units, glutaric anhydride units, and N-substituted or unsubstituted glutarimide units in the main chain, and 7 to 30 mass% of α-methylstyrene units, and 1 to 49 mass% of a methacrylic resin (B). [8] The methacrylic copolymer composition according to [7], wherein the structural unit (R) is an N-substituted or unsubstituted glutarimide unit represented by formula (1): [ka] (In formula (1), R 1 are each independently a hydrogen atom or a methyl group, R 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [9] The methacrylic copolymer composition according to [7] or [8], having a glass transition temperature of 120° C. or higher.
[10] The methacrylic copolymer composition according to any one of [7] to [9], which has a saturated water absorption of 2.5% or less.
[11] The methacrylic copolymer composition according to any one of [7] to
[10] , wherein a melt flow rate of a molded product measured at 230°C under a load of 3.8 kg according to the method specified in JIS K7210 is 1.0 g / 10 min or more.
[12] A molded article comprising the methacrylic copolymer according to any one of [1] to [4] or the methacrylic copolymer composition according to any one of [5] to
[11] .
[13] A film comprising the methacrylic copolymer according to any one of [1] to [4], or the methacrylic copolymer composition according to any one of [5] to
[11] .
[14] A laminate having a layer containing the methacrylic copolymer according to any one of [1] to [4] or the methacrylic copolymer composition according to any one of [5] to
[11] , and a layer containing another material.
[15] A step of continuously supplying a reaction raw material including a monomer mixture containing 70 to 93 mass % of methyl methacrylate, 30 to 7 mass % of α-methylstyrene, and 0 to 10 mass % of a copolymerizable monomer, and a radical polymerization initiator, to a tank-type reactor; A step of bulk polymerizing the monomer mixture in a tank reactor to a polymerization conversion rate of 30 to 60 mass % to obtain a reaction product; and removing the monomer mixture in the reaction product; A method for producing the methacrylic copolymer according to any one of [1] to [4], comprising a step of subjecting the obtained precursor polymer to a ring structure-forming reaction. Effect of the Invention
[0009] According to the present invention, it is possible to obtain molded articles, films including optical films, and laminates which have high transparency, low haze, high heat resistance, high elastic modulus, and low water absorption. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Methacrylic copolymer) The methacrylic copolymer of the present invention contains methyl methacrylate units, α-methylstyrene units, and a structural unit (R). The methacrylic copolymer of the present invention further contains copolymerizable monomer units, methacrylic acid amide units represented by the following formula (A), and 2-(hydroxyalkyl)acrylic acid ester units represented by the following formula (B).
[0011] [ka] (In the formula, R 2 , R 4 , R 5 is defined below) may also include
[0012] In the methacrylic copolymer of the present invention, the proportion of methyl methacrylate units is preferably 40 to 87% by mass, more preferably 50 to 85% by mass, and further preferably 65 to 80% by mass, based on the total structural units. If the proportion of methyl methacrylate units is less than this range, the total light transmittance of the resulting methacrylic copolymer is deteriorated, whereas if the proportion of methyl methacrylate units is more than this range, the heat resistance of the resulting methacrylic copolymer is reduced.
[0013] In the methacrylic copolymer of the present invention, the proportion of α-methylstyrene units is preferably 7 to 30 mass%, more preferably 8 to 27 mass%, and further preferably 11 to 25 mass% based on the total structural units. If the proportion of α-methylstyrene units is less than this range, the saturated water absorption of the resulting methacrylic copolymer is high. In addition, if the proportion of α-methylstyrene units exceeds 30 mass%, the polymerizability is low and the productivity is reduced.
[0014] The structural unit (R) is a structural unit having at least one ring structure selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, and an N-substituted or unsubstituted glutarimide unit in the main chain. The structural unit may contain a methacrylamide unit represented by the above formula (A) and / or a 2-(hydroxyalkyl)acrylic ester unit represented by the above formula (B) in the main chain.
[0015] The lactone ring unit is a structural unit containing a >CH-OC(=O)- group in the ring structure. The structural unit containing a >CH-OC(=O)- group in the ring structure preferably has 4 to 8 ring constituent elements, more preferably 5 to 6, and most preferably 6. Examples of the structural unit containing a >CH-OC(=O)- group in the ring structure include lactone diyl structural units such as β-propiolactone diyl structural unit, γ-butyrolactone diyl structural unit, and δ-valerolactone diyl structural unit. The structural unit containing a >CH-OC(=O)- group in the ring structure can be obtained, for example, by intramolecular cyclization of a polymer having a hydroxy group and an ester group with the hydroxy group and the ester group. In addition, ">C" in the formula means that the carbon atom C has two bonds.
[0016] For example, an example of the δ-valerolactonediyl structural unit is a structural unit represented by formula (I).
[0017] [ka]
[0018] In formula (I), R 3 , R 4 and R 5 are each independently a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include linear or branched alkyl groups, linear or branched aryl groups, -OCOCH 3 R may include a -CN group, an -N group, etc. The organic group may contain a heteroatom such as an oxygen atom. 5 and R 6 is preferably a methyl group, R 7 is preferably a hydrogen atom.
[0019] The lactone ring unit can be incorporated into the methacrylic copolymer by the methods described in JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, JP-A-2005-146084, etc., for example, by intramolecular cyclization of a structural unit derived from a 2-(hydroxyalkyl)acrylic acid ester and a structural unit derived from methyl (meth)acrylate.
[0020] The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. An example of the unit having a 2,6-dioxodihydropyrandiyl structure is a structural unit represented by the formula (II).
[0021] [ka] In formula (II), R 6 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and is preferably a methyl group.
[0022] The unit having a 2,6-dioxodihydropyrandiyl structure can be incorporated into the methacrylic copolymer by the method described in JP 2007-197703 A, JP 2010-96919 A, or the like, for example, by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, or intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate.
[0023] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure. An example of a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure is a structural unit represented by formula (1).
[0024] [ka] In formula (1), R 1 are each independently a hydrogen atom or a methyl group, and preferably a methyl group. 2 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring, and is preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, and more preferably a methyl group, an n-butyl group, or a cyclohexyl group. The structural unit represented by formula (1) can be prepared by reacting the corresponding acid anhydride (IIa) and NHR as shown in scheme (i), for example. 2 It may be produced by a reaction of an imidizing agent represented by the formula (III) or by an intramolecular cyclization reaction of a copolymer having a partial structure represented by the formula (III). It is preferable to heat the copolymer to convert the structural unit represented by the formula (III) to the structural unit represented by the formula (1) by the intramolecular cyclization reaction.
[0025] Scheme (i) [ka] (In the formula, R 1 , R 2is as defined above.)
[0026] The N-substituted or unsubstituted glutarimide unit can be obtained by the method described in WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, JP2008-274187A, etc., specifically, by reacting a structural unit derived from two adjacent methyl methacrylates or a glutaric anhydride unit with an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an aromatic hydrocarbon group-containing amine such as aniline, toluidine, trichloroaniline, etc., an alicyclic hydrocarbon group-containing amine such as cyclohexylamine, etc., urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, etc. Among these, methylamine is preferred.
[0027] In the methacrylic copolymer of the present invention, the ratio of the structural unit (R) to the total structural units is preferably 6 to 30 mass%, more preferably 7.5 to 25 mass%, and even more preferably 8 to 25 mass%. By changing the ratio of the structural unit (R) to methyl methacrylate, the orientation birefringence of the methacrylic copolymer can be changed. In addition, the higher the content of the structural unit (R), the more the heat resistance of the methacrylic copolymer improves, but the flexibility decreases, and the compatibility with other copolymers and moldability tend to decrease.
[0028] In a preferred embodiment of the present invention, the methacrylic copolymer of the present invention may contain methacrylamide units represented by the above formula (A) and 2-(hydroxyalkyl)acrylic ester units represented by the above formula (B) in an amount of preferably 0 to 2 mass%, more preferably 0 to 1.5 mass%, even more preferably 0 to 1.0 mass%, and most preferably 0 to 0.5 mass% based on the total structural units. If the structural units of formula (A) and / or (B) exceed the above range, the saturated water absorption of the obtained methacrylic copolymer will be high, or crosslinked bodies will be formed during molding, resulting in foreign matter defects and a decrease in appearance quality.
[0029] The methacrylic copolymer of the present invention may contain a structural unit (O) other than the methyl methacrylate unit, the α-methylstyrene unit, and the (R). Examples of the structural unit (O) include units derived from vinyl monomers having only one polymerizable carbon-carbon double bond in one molecule, such as (meth)acrylamide, (meth)acrylonitrile, (meth)acrylic acid, and styrene, a structural unit represented by formula (A), and a structural unit represented by formula (B). In the methacrylic copolymer of the present invention, the proportion of the structural unit (O) is preferably 10 mass% or less based on the total structural units. The proportions of the methyl methacrylate unit, the α-methylstyrene unit, the structural unit (R), and the structural unit (O) are as follows: 1 It can be measured by H-NMR or the like.
[0030] The methacrylic copolymer of the present invention has a weight average molecular weight (Mw) of preferably 40,000 to 200,000, more preferably 50,000 to 180,000, and further preferably 55,000 to 160,000. When Mw is 40,000 or more, the strength, toughness, etc. of the molded article of the present invention are improved. When Mw is 200,000 or less, the flowability of the methacrylic copolymer of the present invention is improved, and molding processability is improved.
[0031] The weight average molecular weight (Mw) is a value calculated by converting a chromatogram measured by gel permeation chromatography into the molecular weight of standard polystyrene.
[0032] The methacrylic copolymer of the present invention has an acid value of preferably 0.01 to 0.30 mmol / g, more preferably 0.05 to 0.28 mmol / g. The acid value is a value proportional to the content of carboxylic acid units and carboxylic anhydride units in the methacrylic copolymer. The acid value can be calculated, for example, by the method described in JP-A-2005-23272. When the acid value is within the above range, the balance of heat resistance, mechanical properties, and moldability is excellent.
[0033] The methacrylic copolymer of the present invention has a glass transition temperature of preferably 130°C as a lower limit, more preferably 131°C, and even more preferably 132°C as an upper limit, and is preferably 160°C, although there is no particular limitation thereto. In this specification, the "glass transition temperature (Tg)" is measured in accordance with JIS K7121. Specifically, the temperature is raised once to 230°C, then cooled to room temperature, and then the DSC curve is measured under conditions of raising the temperature from room temperature to 230°C at a rate of 10°C / min. The midpoint determined from the DSC curve measured during the second heating is determined as the "glass transition temperature (Tg)".
[0034] The saturated water absorption of methacrylic copolymer is measured under the following conditions. The methacrylic copolymer is press-molded into a sheet with a thickness of 1.0 mm. A test piece of 50 mm x 50 mm is cut out from the center of the obtained press-molded sheet and dried in a dryer at 80 ° C for more than 16 hours. The dried test piece is cooled to room temperature in a desiccator, and its weight is measured to the nearest 0.1 mg, and this weight is the initial weight Wo. The test piece is immersed in distilled water at 23 ° C., and after immersion for 24 hours, the test piece is removed from the water and all surface moisture is wiped off with a clean, dry cloth or filter paper. Within 1 minute of removing from the water, the test piece is weighed again to the nearest 0.1 mg. The test piece is immersed again, and after 24 hours, its weight is measured again in the same manner as above. The weight when the weight change rate of the test piece becomes within 0.02% of Wo is the saturated weight Ws. The saturated water absorption was calculated from formula (2).
[0035]
number
[0036] (Methacrylic copolymer manufacturing method) The methacrylic copolymer of the present invention can be obtained by a method including subjecting a copolymer of methyl methacrylate and α-methylstyrene (hereinafter sometimes referred to as a precursor polymer) to a ring structure-forming reaction. That is, the production method of the present invention comprises the steps of continuously supplying a reaction raw material containing a monomer mixture containing 70 to 93 mass % of methyl methacrylate, 30 to 7 mass % of α-methylstyrene, and 0 to 10 mass % of a copolymerizable monomer, a radical polymerization initiator, and optionally a chain transfer agent, to a tank-type reactor; A step of bulk polymerizing the monomer mixture in a tank reactor to a polymerization conversion rate of 30 to 60 mass % to obtain a reaction product; and removing the monomer mixture in the reaction product; A step of subjecting the obtained precursor polymer to a ring structure forming reaction. Includes.
[0037] The precursor polymer is polymerized from reaction raw materials including a monomer mixture, a radical polymerization initiator, and, if necessary, a chain transfer agent, and the monomer mixture contains 70 to 93 mass %, preferably 75 to 90 mass %, of methyl methacrylate in the monomer mixture. The content of α-methylstyrene is 30 to 7% by mass, and preferably 25 to 10% by mass. The content of the copolymerizable monomer is 0 to 10% by mass, preferably 0 to 5% by mass. The monomer mixture may contain a monomer other than methyl methacrylate and α-methylstyrene. Examples of such monomers include alkyl methacrylate esters other than methyl methacrylate, such as ethyl methacrylate and butyl methacrylate; aryl methacrylate esters such as phenyl methacrylate; cycloalkyl methacrylate esters such as cyclohexyl methacrylate and norbornenyl methacrylate; aryl acrylate esters such as phenyl acrylate; cycloalkyl acrylate esters such as cyclohexyl acrylate and norbornenyl acrylate; aromatic vinyl monomers such as styrene; acrylamide; methacrylamide; acrylonitrile; and vinyl monomers having only one polymerizable alkenyl group in one molecule, such as methacrylonitrile. The content of monomers other than methyl methacrylate and alkyl acrylate esters in the monomer mixture is preferably 10% by mass or less, more preferably 5% by mass or less.
[0038] The monomer mixture preferably has b* of -1 to 2, more preferably -0.5 to 1.5. When b* is in this range, it is advantageous in obtaining molded products with little coloring at high production efficiency when the resulting methacrylic copolymer composition is molded. Note that b* is a value measured in accordance with the International Commission on Illumination (CIE) standard (1976) or JIS Z-8722. The monomer mixture removed from the reaction product by the step of removing the monomer mixture in the reaction product can be recovered and reused in the present invention. If the b* of the recovered monomer mixture becomes high due to heat applied during recovery, it is preferable to purify the monomer mixture by an appropriate method to make the b* within the above range.
[0039] The polymerization initiator used in the present invention is not particularly limited as long as it generates reactive radicals. For example, t-hexylperoxyisopropylmonocarbonate, t-hexylperoxy2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, 1,1,3,3-tetramethylbutylperoxyneodecanoate, 1,1-bis(t-hexylperoxy)cyclohexane, benzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, lauroyl peroxide, 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methylbutyronitrile), dimethyl 2,2'-azobis(2-methylpropionate) are preferred; More preferred are t-hexylperoxy 2-ethylhexanoate, 1,1-bis(t-hexylperoxy)cyclohexane, and dimethyl 2,2'-azobis(2-methylpropionate).
[0040] The polymerization initiator used in the present invention has an average uncleaved initiator concentration (I) of 5.1×10 at the polymerization temperature in a tank reactor described below. -5 ~2.4×10 -4 (mol / L) range is desirable.
[0041] The amount of the polymerization initiator used is adjusted to the polymerization temperature and added to the monomer mixture so as to obtain the above initiator concentration (I).
[0042] Examples of the chain transfer agent used in the present invention include alkyl mercaptans such as n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, 1,4-butanedithiol, 1,6-hexanedithiol, ethylene glycol bisthiopropionate, butanediol bisthioglycolate, butanediol bisthiopropionate, hexanediol bisthioglycolate, hexanediol bisthiopropionate, trimethylolpropane tris-(β-thiopropionate), and pentaerythritol tetrakisthiopropionate; terpinolene, etc. Among these, monofunctional alkyl mercaptans such as n-octyl mercaptan and n-dodecyl mercaptan are preferred. These chain transfer agents can be used alone or in combination of two or more. The amount of the chain transfer agent used is preferably 0 to 1 part by mass, more preferably 0.01 to 0.8 parts by mass, and further preferably 0.02 to 0.6 parts by mass, based on 100 parts by mass of the monomer mixture.
[0043] In principle, no solvent is used in bulk polymerization, but when it is necessary to adjust the viscosity of the reaction liquid, a solvent can be included in the monomer mixture. As the solvent, aromatic hydrocarbons such as benzene, toluene, and ethylbenzene are preferable. These solvents can be used alone or in combination of two or more. The amount of such a solvent to be used is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the monomer mixture.
[0044] The reaction raw material used in the present invention has a dissolved oxygen content of preferably 10 ppm or less, more preferably 5 ppm or less, further preferably 4 ppm or less, and most preferably 3 ppm or less. If the dissolved oxygen content is within such a range, the polymerization reaction proceeds smoothly, and molded products without silver streaks or coloring can be easily obtained.
[0045] The temperature inside the tank reactor, i.e., the temperature of the liquid inside the reaction tank, is preferably 110 to 140° C., more preferably 114 to 135° C. If the temperature is higher than this range, it becomes difficult to produce high molecular weight compounds containing α-methylstyrene, which causes a decrease in heat resistance.
[0046] The water content in the reaction liquid in the tank reactor is preferably 1000 ppm or less, more preferably 700 ppm or less, and even more preferably 280 ppm or less. By keeping the water content at 1000 ppm or less, it is possible to suppress the generation of resin foreign matter of several μm to several tens of μm during the polymerization reaction, and when the obtained methacrylic copolymer composition is formed into a film or sheet by melt molding, it is possible to significantly reduce the occurrence of defects having an outer diameter of several tens of μm caused by the resin foreign matter.
[0047] In a tank reactor, bulk polymerization is preferably carried out until the polymerization conversion rate reaches 30 to 65% by mass, and more preferably 35 to 60% by mass.
[0048] The average residence time (θ) of the reaction raw materials in the tank reactor is preferably 1.5 to 5 hours, more preferably 2 to 4.5 hours, and even more preferably 2.5 to 4 hours. If the average residence time is too short, the amount of polymerization initiator required increases. Furthermore, an increase in the amount of polymerization initiator makes it difficult to control the polymerization reaction and tends to make it difficult to control the molecular weight. On the other hand, if the average residence time is too long, it takes time for the reaction to reach a steady state, and productivity tends to decrease. The average residence time can be adjusted by the capacity of the tank reactor and the amount of reaction raw materials supplied.
[0049] The bulk polymerization is preferably carried out in an atmosphere of an inert gas such as nitrogen gas.
[0050] The manufacturing method of the present invention has a step of removing the monomer mixture in the reaction product. Here, the reaction product is not limited to the reaction product obtained by bulk polymerization in a tank reactor, and may be a reaction product obtained in another reactor connected after the tank reactor as necessary, that is, a reaction product in which the unreacted monomer mixture in the reaction product obtained by bulk polymerization in a tank reactor is further polymerized in another reactor to increase the polymerization conversion rate. In addition, in this step, the solvent is also removed at the same time as necessary. Although the removal method is not particularly limited, a thermal devolatilization method is preferred. Examples of the thermal devolatilization method include an equilibrium flash evaporation method and an adiabatic flash evaporation method, and the adiabatic flash evaporation method is preferred. The temperature at which the adiabatic flash evaporation method is performed is preferably 200 to 280°C, more preferably 220 to 280°C, and even more preferably 220 to 270°C. If the temperature at which the adiabatic flash evaporation method is performed is less than 200°C, it takes a long time to devolatilize, and the devolatilization becomes insufficient, which may cause poor appearance such as silver streaks on the molded product. On the other hand, when the temperature at which the adiabatic flash evaporation method is carried out exceeds 280°C, the methacrylic copolymer composition tends to be colored and depolymerized due to oxidation, burning, decomposition, etc. The adiabatic flash evaporation method may be carried out in multiple stages. In this case, the reaction product flowing through the heat transfer tube is heated with the vapor of the flash-evaporated monomer mixture, and the heated reaction product can be supplied to a low-pressure flash tank for flash evaporation. The reaction product can be pressurized by a pump or the like. After removing the monomer mixture, the methacrylic copolymer composition can be made into pellets or powder particles according to a known method to facilitate ease of handling as a molding material. The content of the monomer mixture in the methacrylic copolymer composition obtained by the present invention is preferably 1% by mass or less, more preferably 0.5% by mass or less.
[0051] The precursor polymer has a glass transition temperature of preferably 124°C as a lower limit, more preferably 125°C, and further preferably 127°C as an upper limit, and preferably 150°C. The glass transition temperature can be changed by adjusting the molecular weight, the amount of α-methylstyrene copolymerized, and the like. The higher the glass transition temperature of the precursor polymer, the more improved the heat resistance. A methacrylic copolymer obtained by using a precursor polymer having a high glass transition temperature has high heat resistance even if the amount of structural unit (R) is small, and is therefore unlikely to cause deterioration of saturated water absorption, etc.
[0052] The precursor polymer is not particularly limited as long as the total content of structural units derived from methyl methacrylate is 70 to 93% by mass and the total content of structural units derived from α-methylstyrene is 30 to 7% by mass. From the viewpoint of polymerizability, transparency, etc., the total content of structural units derived from methyl methacrylate in the precursor polymer is preferably 73% by mass or more and 93% by mass or less, more preferably 75% by mass or more and 92% by mass or less, and most preferably 80% by mass or more and 92% by mass or less. From the viewpoint of heat resistance, polymerizability, water absorption, etc., the total content of structural units derived from α-methylstyrene in the precursor polymer is preferably 7% by mass or more and 27% by mass or less, more preferably 8% by mass or more and 25% by mass or less. If the structural units derived from α-methylstyrene are less than this range, sufficient heat resistance cannot be obtained, and if they are more than this range, the polymerizability is significantly reduced.
[0053] The precursor polymer has a polystyrene-equivalent weight average molecular weight Mw of preferably 30,000 to 200,000, more preferably 40,000 to 180,000, and even more preferably 50,000 to 160,000 in a chromatogram obtained by gel permeation chromatography. If the weight average molecular weight Mw is smaller than this range, the resulting molded article becomes brittle, and if it is higher than this range, the productivity deteriorates. Mw can be controlled by adjusting the type, amount, and addition timing of the polymerization initiator and chain transfer agent (optional components) used in the production of the precursor polymer.
[0054] The ring structure forming reaction can be carried out, for example, using an extruder. Examples of the extruder include a single screw extruder, a twin screw extruder, and a multi-screw extruder. From the viewpoint of mixing performance, a twin screw extruder is preferred. Twin screw extruders include non-intermeshing co-rotating type, intermeshing co-rotating type, non-intermeshing counter-rotating type, and intermeshing counter-rotating type. The intermeshing co-rotating type is preferred because it can rotate at high speed and can efficiently promote mixing. These extruders may be used alone or connected in series.
[0055] In the ring structure forming reaction using an extruder, for example, a precursor polymer as a raw material is fed from the raw material inlet of the extruder, the precursor polymer is melted, and the cylinder is filled with the precursor polymer. Then, an imidizing agent (optional component) and the like are injected into the extruder using an addition pump, whereby the ring structure forming reaction can proceed in the extruder. When an imidizing agent is used, the structural unit (R) contains an N-substituted or unsubstituted glutarimide unit, and may contain a lactone ring unit and / or a glutaric anhydride unit as necessary. When an imidizing agent is not used, the structural unit (R) is composed of a lactone ring unit and / or a glutaric anhydride unit. A preferred imidizing agent is R 4 -NH 2 (R 4 is as defined above). The imidizing agent is used in an amount of 1.6 to 12 parts by mass per 100 parts by mass of the methacrylic copolymer. When the amount of the imidizing agent used is within the above range, the by-production of methacrylic acid amide units can be suppressed.
[0056] The resin temperature in the reaction zone in the extruder is preferably in the range of 180 to 280°C, more preferably in the range of 200 to 280°C. If the resin temperature in the reaction zone is less than 180°C, the heat resistance of the methacrylic copolymer tends to decrease due to a decrease in the reaction efficiency of the ring structure formation reaction, the by-production of methacrylamide units, etc. If the resin temperature in the reaction zone exceeds 280°C, the resin decomposition becomes significant, and the mechanical strength, such as the tensile breaking strength, of the molded body and film made of the obtained methacrylic copolymer tends to decrease. The reaction zone in the extruder refers to the region between the injection position of the imidizing agent, etc., in the cylinder of the extruder to the resin discharge port (die part).
[0057] By increasing the reaction time in the reaction zone of the extruder, the ring structure forming reaction can be promoted. The reaction time in the reaction zone of the extruder is preferably longer than 10 seconds, and more preferably longer than 30 seconds. If the reaction time is less than 10 seconds, the ring structure forming reaction may hardly proceed.
[0058] The resin pressure in the extruder is preferably in the range of atmospheric pressure to 50 MPa, and more preferably in the range of 1 to 30 MPa. If it is 50 MPa or more, it exceeds the limit of the mechanical pressure resistance of a normal extruder, and a special device is required, which is not preferable from the viewpoint of cost.
[0059] It is preferable to use an extruder having a vent hole that can reduce the pressure to below atmospheric pressure. With such a configuration, unreacted materials, by-products such as methanol, and monomers can be removed, and the breaking strength of a molded article containing the methacrylic copolymer of the present invention tends to be improved.
[0060] For the ring structure-forming reaction, a horizontal twin-screw reactor such as Bivolac manufactured by Sumitomo Heavy Industries, Ltd. or a vertical twin-screw stirring tank such as Superblend, which is suitable for high viscosity reaction, can be suitably used instead of an extruder.
[0061] During the ring structure forming reaction, a carboxyl group may be by-produced in the methacrylic copolymer. This carboxyl group may be converted to an ester group by an esterifying agent or a catalyst, if necessary. This can reduce foaming of the resin during the production of an optical film. The ester group varies depending on the esterifying agent and catalyst used, but from the viewpoints of reducing the resin melt viscosity during melt molding, the reactivity of esterification, and the heat resistance of the resin after esterification, it is preferable that the ester group contains a methyl methacrylate unit, and more preferably contains both a methyl methacrylate unit and an ethyl methacrylate unit. As the esterifying agent, dimethyl carbonate is preferred from the viewpoints of cost, reactivity, etc.
[0062] The amount of the esterifying agent added can be set, for example, so that the acid value of the methacrylic copolymer becomes a desired value.
[0063] In addition to the esterification agent, a catalyst can be used in combination. The type of catalyst is not particularly limited, but examples thereof include amine compounds such as trimethylamine, triethylamine, monomethyldiethylamine, and dimethylmonoethylamine. Among these, triethylamine is preferred from the viewpoints of cost, reactivity, and the like.
[0064] (Methacrylic copolymer composition) In a preferred embodiment of the present invention, the methacrylic copolymer composition of the present invention contains a methacrylic copolymer (A) and a methacrylic resin (B). The mass ratio of the methacrylic copolymer (A) / methacrylic resin (B) is 99 / 1 to 51 / 49, preferably 95 / 5 to 55 / 45, and more preferably 90 / 10 to 60 / 40, from the viewpoint of heat resistance and fluidity. When the content of the methacrylic copolymer (A) in the methacrylic copolymer composition of the present invention is 51% by mass or more, the composition has excellent heat resistance and surface hardness, and when the content is 99% by mass or less, the composition has improved fluidity.
[0065] (Methacrylic copolymer (A)) As the methacrylic copolymer (A) according to the present invention, the above-mentioned copolymers can be used. (Methacrylic resin (B)) The content of the methacrylic resin (B) in the methacrylic copolymer composition of the present invention is 1 to 49% by mass, preferably 5 to 45% by mass, and more preferably 10 to 40% by mass. The methacrylic copolymer composition of the present invention has improved flowability due to the content of the methacrylic resin (B) being in the range of 1 to 49% by mass.
[0066] The methacrylic resin (B) is a resin containing a structural unit derived from a methacrylic acid ester. Examples of such methacrylic acid esters include methacrylic acid alkyl esters such as methyl methacrylate (hereinafter referred to as "MMA"), ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, and dodecyl methacrylate; and methacrylic acid alkyl esters such as 1-methylcyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, and tricyclo[5.2.1.0] methacrylate. 2,6 ] methacrylic acid cycloalkyl esters such as deca-8-yl; methacrylic acid aryl esters such as phenyl methacrylate; methacrylic acid aralkyl esters such as benzyl methacrylate; and the like. From the viewpoint of availability, MMA, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, and tert-butyl methacrylate are preferred, and MMA is the most preferred. Methacrylic acid esters can be used alone or in combination of two or more. The content of structural units derived from methacrylic acid esters in the methacrylic resin (B) is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more, and may be only structural units derived from methacrylic acid esters.
[0067] From the viewpoint of heat resistance, the methacrylic resin (B) preferably contains structural units derived from MMA in an amount of 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99.5% by mass or more, and may contain only structural units derived from MMA.
[0068] The methacrylic resin (B) may contain a structural unit derived from a monomer other than the methacrylic acid ester. The other monomer is preferably an acrylic acid ester. The content of the structural unit derived from the acrylic acid ester in the methacrylic resin (B) is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 2% by mass or less, and most preferably 0.5% by mass or less.
[0069] Examples of such acrylic acid esters include methyl acrylate (hereinafter referred to as "MA"), ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, dodecyl acrylate, stearyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, cyclohexyl acrylate, 2-methoxyethyl acrylate, 3-methoxybutyl acrylate, trifluoromethyl acrylate, trifluoroethyl acrylate, pentafluoroethyl acrylate, glycidyl acrylate, allyl acrylate, phenyl acrylate, toluyl acrylate, benzyl acrylate, isobornyl acrylate, and 3-dimethylaminoethyl acrylate. From the viewpoint of availability, MA, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, and tert-butyl acrylate are preferred, MA and ethyl acrylate are more preferred, and MA is most preferred. The acrylic acid esters can be used alone or in combination of two or more kinds.
[0070] The methacrylic resin (B) is obtained by polymerizing the above-mentioned methacrylic acid ester and other optional monomers. In the case of using a plurality of types of monomers in this polymerization, usually, the plurality of types of monomers are mixed to prepare a monomer mixture, which is then subjected to polymerization. There is no particular restriction on the polymerization method, but from the viewpoint of productivity, it is preferable to carry out radical polymerization by a method such as bulk polymerization, suspension polymerization, solution polymerization, or emulsion polymerization.
[0071] The lower limit of the syndiotacticity (rr) of the methacrylic resin (B) expressed as a triad is preferably 56% or more, more preferably 57% or more, and even more preferably 58% or more. When the lower limit of the content of such a structure is 56% or more, the methacrylic copolymer composition of the present invention has excellent heat resistance.
[0072] Here, syndiotacticity (rr) expressed by a triad (hereinafter sometimes simply referred to as "syndiotacticity (rr)") is the proportion of two chains (diads, diads) in a chain of three consecutive structural units (triad) that are both racemo (denoted as rr). Note that in the chains (diads, diads) of structural units in a polymer molecule, those with the same stereoconfiguration are called meso, and those with the opposite stereoconfiguration are called racemo, and are denoted as m and r, respectively. The syndiotacticity (rr) (%) of the methacrylic resin (B) in deuterated chloroform at 30°C is 1 The H-NMR spectrum is measured, and the area (X) of the region from 0.6 to 0.95 ppm and the area (Y) of the region from 0.6 to 1.35 ppm are measured from the spectrum when tetramethylsilane (TMS) is set to 0 ppm, and the amount of the hydrogen can be calculated using the formula: (X / Y)×100.
[0073] The weight average molecular weight (hereinafter referred to as "Mw") of the methacrylic resin (B) is preferably 40,000 to 300,000, more preferably 45,000 to 200,000, and even more preferably 50,000 to 150,000. When the Mw is 40,000 or more, the methacrylic copolymer composition of the present invention has excellent mechanical strength, and when it is 400,000 or less, the methacrylic copolymer composition of the present invention has excellent flowability, and the molding processability of the methacrylic copolymer composition of the present invention can be improved.
[0074] The glass transition temperature of the methacrylic resin (B) is preferably 110° C. or higher, more preferably 115° C. or higher, and even more preferably 120° C. or higher. When the glass transition temperature is 110° C. or higher, the methacrylic copolymer composition of the present invention has excellent heat resistance. In this specification, the glass transition temperature is a temperature measured using a differential scanning calorimeter at a heating rate of 10° C. / min and calculated by the midpoint method.
[0075] The saturated water absorption of the methacrylic resin (B) in 23°C water is preferably 2.5% by mass or less, more preferably 2.3% by mass or less, and even more preferably 2.1% by mass or less. When the saturated water absorption is 2.5% by mass or less, the methacrylic copolymer composition of the present invention has excellent moisture resistance and can suppress dimensional changes caused by moisture absorption. The saturated water absorption in this specification is a value measured by immersing a molded product in distilled water at 23°C, measuring the mass over time, and measuring the mass at the time of reaching equilibrium, relative to the mass of the molded product vacuum-dried for 3 days or more.
[0076] The melt flow rate (hereinafter referred to as "MFR") of the methacrylic resin (B) is preferably in the range of 1 to 30 g / 10 min. The lower limit of the MFR is more preferably 1.2 g / 10 min or more, and even more preferably 1.5 g / 10 min. The upper limit of the MFR is more preferably 25 g / 10 min or less, and even more preferably 22 g / 10 min or less. When the MFR is in the range of 1 to 30 g / 10 min, the stability of the hot melt molding is good. In this specification, the MFR is a value measured at a temperature of 230°C and a load of 3.8 kg using a melt indexer in accordance with JIS K7210.
[0077] The methacrylic copolymer composition of the present invention has a melt flow rate at 230° C. under a load of 3.8 kg of preferably 1 g / 10 min or more, more preferably 1.5 to 20 g / 10 min, and further preferably 2 to 10 g / 10 min. The melt flow rate is a melt mass flow rate value measured in accordance with JIS K7210.
[0078] The methacrylic copolymer composition of the present invention has a glass transition temperature of preferably 120 to 160° C., more preferably 125 to 155° C., and further preferably 130 to 150° C. If the glass transition temperature is 120° C. or lower, the heat resistance and the like tend to decrease, and if the glass transition temperature is 160° C. or higher, the moldability and the like tend to decrease.
[0079] The methacrylic copolymer composition of the present invention has a softening temperature of a molded article measured by the method specified in JIS K7206 B50 method of preferably 115° C. or higher, more preferably 120° C. or higher, and even more preferably 125° C. or higher. When the softening temperature is 115° C. or higher, the molded article has excellent heat resistance and excellent dimensional stability at high temperatures.
[0080] The methacrylic copolymer composition of the present invention has a saturated water absorption of 2.5% or less, more preferably 2.1% or less, and even more preferably 2.0% or less, measured under the same conditions as those for the saturated water absorption of the methacrylic copolymer (A). The saturated water absorption of 2.5% or less provides excellent dimensional stability under high humidity conditions.
[0081] The methacrylic copolymer composition of the present invention may contain a filler as necessary within a range that does not impair the effects of the present invention. Examples of the filler include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of the filler that can be contained in the copolymer composition of the present invention is preferably 3 mass% or less, more preferably 1.5 mass% or less.
[0082] The methacrylic copolymer composition of the present invention may contain other polymers within the range that does not impair the effects of the present invention. Examples of other polymers include polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene-based ionomers; styrene-based resins such as polystyrene, styrene-maleic anhydride copolymer, high impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate-styrene copolymers; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyamides such as nylon 6, nylon 66, and polyamide elastomers; polyvinyl chloride and polyvinyl chloride. Examples of the other polymers that can be contained in the copolymer composition of the present invention include polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyacetal, polyvinylidene fluoride, polyurethane, phenoxy resin, modified polyphenylene ether, polyphenylene sulfide, silicone modified resin, silicone rubber, acrylic multilayer copolymer elastomer, acrylic thermoplastic elastomers such as diblock copolymers and triblock copolymers of methyl methacrylate polymer block-n-butyl acrylate polymer block, styrene thermoplastic elastomers such as SEPS, SEBS, SIS, and olefin rubbers such as IR, EPR, EPDM, etc. The amount of other polymers that can be contained in the copolymer composition of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and most preferably 0% by mass.
[0083] The methacrylic copolymer composition of the present invention may contain additives generally used in resin compositions, provided that the object of the present invention is not impaired. Examples of additives include fillers, antioxidants, heat deterioration inhibitors, UV absorbers, light stabilizers, lubricants, release agents, polymer processing aids, antistatic agents, flame retardants, colorants, dyes, pigments, light diffusing agents, organic dyes, matting agents, impact resistance modifiers, and fluorescent materials. The total amount of such additives other than fillers is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less.
[0084] Examples of the filler include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of the filler that can be contained in the methacrylic copolymer composition of the present invention is preferably 3% by mass or less, more preferably 1.5% by mass or less.
[0085] The antioxidant is effective in preventing the oxidative deterioration of the resin by itself in the presence of oxygen. Examples of the antioxidant include phosphorus-based antioxidants, hindered phenol-based antioxidants, and thioether-based antioxidants. These antioxidants can be used alone or in combination of two or more. Among these, from the viewpoint of the effect of preventing the deterioration of optical properties due to coloring, phosphorus-based antioxidants and hindered phenol-based antioxidants are preferred, and the combined use of a phosphorus-based antioxidant and a hindered phenol-based antioxidant is more preferred. When the phosphorus-based antioxidant and the hindered phenol-based antioxidant are used in combination, their ratio is not particularly limited, but the mass ratio of the phosphorus-based antioxidant / the hindered phenol-based antioxidant is preferably 1 / 5 to 2 / 1, and more preferably 1 / 2 to 1 / 1.
[0086] Examples of phosphorus-based antioxidants include 2,2-methylenebis(4,6-di-t-butylphenyl)octyl phosphite (manufactured by ADEKA Corporation; trade name: Adeka STAB HP-10), tris(2,4-di-t-butylphenyl)phosphite (manufactured by Ciba Specialty Chemicals Corporation; trade name: IRUGA FOS 168), and 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (manufactured by ADEKA Corporation; trade name: Adeka STAB PEP-36).
[0087] Examples of the hindered phenol antioxidant include pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1010) and octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1076).
[0088] The heat deterioration inhibitor is capable of preventing the thermal deterioration of a resin by capturing polymer radicals that are generated when the resin is exposed to high heat in a substantially oxygen-free state. Examples of the heat deterioration inhibitor include 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-hydroxybenzyl)-4-methylphenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GM) and 2,4-di-tert-amyl-6-(3',5'-di-tert-amyl-2'-hydroxy-α-methylbenzyl)phenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GS).
[0089] An ultraviolet absorber is a compound that has the ability to absorb ultraviolet rays. An ultraviolet absorber is a compound that is said to have the function of converting light energy into heat energy. Examples of ultraviolet absorbents include benzophenones, benzotriazoles, triazines, benzoates, salicylates, cyanoacrylates, oxalic anilides, malonic acid esters, and formamidines. These may be used alone or in combination of two or more. Among these, benzotriazoles, triazines, or compounds having a maximum molar absorption coefficient ε at a wavelength of 380 to 450 nm are preferred. max 1200dm 3 mol -1 cm -1 Preferred are UV absorbers which are:
[0090] Benzotriazoles are highly effective in suppressing the deterioration of optical properties such as coloring caused by ultraviolet rays, and are therefore preferred as ultraviolet absorbing agents when the film of the present invention is applied to optical applications.As benzotriazoles, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (manufactured by BASF; trade name TINUVIN329), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (manufactured by BASF; trade name TINUVIN234), 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol] (manufactured by ADEKA; trade name LA-31), 2-(5-octylthio-2H-benzotriazol-2-yl)-6-tert-butyl-4-methylphenol, etc. are preferred.
[0091] In addition, the maximum molar absorption coefficient ε max 1200dm 3 mol -1 cm -1 The following ultraviolet absorbents can suppress the yellowing of the resulting molded product. Examples of such ultraviolet absorbents include 2-ethyl-2'-ethoxy-oxalanilide (manufactured by Clariant Japan; product name: Sandubor VSU). Among these ultraviolet absorbents, benzotriazoles are preferably used from the viewpoint of suppressing resin deterioration due to ultraviolet rays.
[0092] In addition, when it is desired to efficiently absorb short wavelengths of 380 nm or less, triazine ultraviolet absorbers are preferably used. Examples of such ultraviolet absorbers include 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine (manufactured by ADEKA; product name LA-F70), its analogues, hydroxyphenyltriazine ultraviolet absorbers (manufactured by BASF; product names TINUVIN477, TINUVIN460, and TINUVIN479), and 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine.
[0093] Furthermore, when it is desired to particularly effectively absorb light with a wavelength of 380 to 400 nm, it is preferable to use a metal complex having a ligand with a heterocyclic structure as disclosed in WO2011 / 089794A1, WO2012 / 124395A1, JP2012-012476A, JP2013-023461A, JP2013-112790A, JP2013-194037A, JP2014-62228A, JP2014-88542A, JP2014-88543A, or the like, as an ultraviolet absorber.
[0094] Examples of the ligand having the heterocyclic structure include 2,2'-iminobisbenzothiazole, 2-(2-benzothiazolylamino)benzoxazole, 2-(2-benzothiazolylamino)benzimidazole, (2-benzothiazolyl)(2-benzimidazolyl)methane, bis(2-benzoxazolyl)methane, bis(2-benzothiazolyl)methane, bis[2-(N-substituted)benzimidazolyl]methane, and derivatives thereof. As the central metal of such a metal complex, copper, nickel, cobalt, and zinc are preferably used. In addition, in order to use these metal complexes as ultraviolet absorbents, it is preferable to disperse the metal complex in a medium such as a low molecular weight compound or a polymer. The amount of the metal complex to be added is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the film of the present invention. Since the molar absorption coefficient of the metal complex at wavelengths of 380 to 400 nm is large, a small amount of the metal complex to be added can be used to obtain a sufficient ultraviolet absorbing effect. If the amount of the metal complex is small, deterioration of the appearance of the molded product due to bleeding out can be suppressed. In addition, since the metal complex has high heat resistance, deterioration and decomposition during molding are small. Furthermore, since the metal complex has high light resistance, the ultraviolet absorbing performance can be maintained for a long period of time.
[0095] The maximum molar absorption coefficient ε of the ultraviolet absorber maxThe molecular weight (M) of the ultraviolet absorber is measured as follows. 10.00 mg of the ultraviolet absorber is added to 1 L of cyclohexane, and dissolved until no undissolved matter is found by visual observation. The solution is poured into a quartz glass cell measuring 1 cm x 1 cm x 3 cm, and the absorbance at wavelengths of 380 to 450 nm is measured using a spectrophotometer (Hitachi, Ltd.; product name U-3410). UV ) and the maximum absorbance measured (A max ) and the maximum molar absorption coefficient ε max Calculate. ε max =[A max / (10×10 -3 )]×M UV
[0096] A light stabilizer is a compound that is said to have the function of capturing radicals generated mainly by oxidation due to light. Suitable light stabilizers include hindered amines such as compounds having a 2,2,6,6-tetraalkylpiperidine skeleton.
[0097] Examples of the lubricant include stearic acid, behenic acid, stearamide acid, methylene bisstearamide, hydroxystearic acid triglyceride, paraffin wax, ketone wax, octyl alcohol, and hardened oil.
[0098] Examples of the release agent include higher alcohols such as cetyl alcohol and stearyl alcohol; and higher fatty acid esters of glycerin such as monoglyceride stearate and diglyceride stearate. In the present invention, it is preferable to use higher alcohols and glycerin fatty acid monoesters in combination as the release agent. When higher alcohols and glycerin fatty acid monoesters are used in combination, the ratio is not particularly limited, but the amount of higher alcohols used: the amount of glycerin fatty acid monoester used is preferably 2.5:1 to 3.5:1, more preferably 2.8:1 to 3.2:1, by mass ratio.
[0099] The polymer processing aid is a compound that is effective in achieving thickness accuracy and thinning when molding a methacrylic copolymer composition. The polymer processing aid can usually be produced by an emulsion polymerization method. The polymer processing aid is preferably a polymer particle having a particle size of 0.05 to 0.5 μm. The polymer particles may be single-layer particles made of a polymer with a single composition ratio and a single intrinsic viscosity, or may be multi-layer particles made of two or more polymers with different composition ratios or intrinsic viscosities. Among these, preferred are particles with a two-layer structure having a polymer layer with a low intrinsic viscosity as an inner layer and a polymer layer with a high intrinsic viscosity of 5 dl / g or more as an outer layer. The polymer processing aid preferably has an intrinsic viscosity of 3 to 6 dl / g. If the intrinsic viscosity is too low, the effect of improving moldability is low. If the intrinsic viscosity is too high, the melt flowability of the methacrylic copolymer composition is likely to decrease. Examples of the antistatic agent include alkylsulfonates such as sodium heptyl sulfonate, sodium octyl sulfonate, sodium nonyl sulfonate, sodium decyl sulfonate, sodium dodecyl sulfonate, sodium cetyl sulfonate, sodium octadecyl sulfonate, sodium diheptyl sulfonate, potassium heptyl sulfonate, potassium octyl sulfonate, potassium nonyl sulfonate, potassium decyl sulfonate, potassium dodecyl sulfonate, potassium cetyl sulfonate, potassium octadecyl sulfonate, potassium diheptyl sulfonate, lithium heptyl sulfonate, lithium octyl sulfonate, lithium nonyl sulfonate, lithium decyl sulfonate, lithium dodecyl sulfonate, lithium cetyl sulfonate, lithium octadecyl sulfonate, and lithium diheptyl sulfonate. Examples of the flame retardant include metal hydrates having a hydroxyl group or crystal water, such as magnesium hydroxide, aluminum hydroxide, hydrated aluminum silicate, hydrated magnesium silicate, and hydrotalcite; phosphate compounds, such as polyamine phosphoric acid esters; and silicon compounds. Of these, preferred are phosphate ester-based flame retardants, such as trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, dimethylethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, and hydroxyphenyl diphenyl phosphate. Examples of dyes and pigments include red organic pigments such as Para Red, Fire Red, Pyrazolone Red, Thioindigo Red, and Perylene Red; blue organic pigments such as Cyanine Blue and Indanthrene Blue; and green organic pigments such as Cyanine Green and Naphthol Green. One or more of these can be used.
[0100] As the organic dye, a compound having a function of converting ultraviolet light into visible light is preferably used. Examples of the light diffusing agent and the matting agent include glass particles, polysiloxane-based crosslinked particles, crosslinked polymer particles, talc, calcium carbonate, and barium sulfate. Examples of fluorescent materials include fluorescent pigments, fluorescent dyes, fluorescent white dyes, fluorescent brighteners, and fluorescent bleaches.
[0101] These additives may be used alone or in combination of two or more. These additives may be added to the polymerization reaction solution when producing the methacrylic copolymer (A) and the methacrylic resin (B), or may be added to the produced methacrylic copolymer (A) and the methacrylic resin (B), or may be added when preparing the methacrylic copolymer composition of the present invention. The total amount of additives contained in the methacrylic copolymer composition of the present invention is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less, based on the methacrylic copolymer composition, from the viewpoint of suppressing defective appearance of the molded article.
[0102] The methacrylic copolymer composition according to one embodiment of the present invention is not particularly limited by its production method, and can be produced, for example, by melt-kneading the methacrylic copolymer of the present invention with additives such as an ultraviolet absorber, and, if necessary, with other polymers. The melt-kneading can be carried out using a melt-kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer. The temperature during kneading can be appropriately set according to the softening temperatures of the methacrylic copolymer and the other polymers, and can be set, for example, to 150 to 300°C. The shear rate during kneading can be set, for example, to 10 to 5000 sec -1 can be set to.
[0103] The method for preparing the methacrylic copolymer composition of another embodiment of the present invention containing the methacrylic resin (B) is not particularly limited. For example, a method of polymerizing a monomer mixture containing methyl methacrylate or the like in the presence of the methacrylic resin (B) to produce the methacrylic copolymer (A), or a method of melt-kneading the methacrylic copolymer (A) and the methacrylic resin (B) can be mentioned. During melt-kneading, other polymers and additives may be mixed as necessary, the methacrylic copolymer (A) may be mixed with the methacrylic resin (B) after mixing with the other polymers and additives, the methacrylic resin (B) may be mixed with the methacrylic copolymer (A) after mixing with the other polymers and additives, or the methacrylic resin (B) may be mixed with the methacrylic copolymer (A), or other methods may be used. The kneading can be performed using a known mixing or kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer. Of these, a twin-screw extruder is preferred.
[0104] The methacrylic copolymer composition of the present invention can be made into a form such as pellets in order to enhance convenience in storage, transportation, or molding.
[0105] (Molded body) The molded article of the present invention includes the methacrylic copolymer or methacrylic copolymer composition of the present invention. The manufacturing method of the molded article of the present invention is not particularly limited. For example, melt molding methods such as the T-die method (lamination method, coextrusion method, etc.), inflation method (coextrusion method, etc.), compression molding method, blow molding method, calendar molding method, vacuum molding method, injection molding method (insert method, two-color method, press method, core-back method, sandwich method, etc.), and solution casting method can be mentioned. Among these, the T-die method, inflation method, and injection molding method are preferred from the viewpoint of high productivity, cost, etc. There is no limitation on the type of molded article, but films (planar molded articles having a thickness of 5 μm to 250 μm) and sheets (planar molded articles thicker than 250 μm) are preferred, and among them, films are particularly preferred.
[0106] The film, which is one form of the molded article of the present invention, can be produced by a solution casting method, a melt casting method, an extrusion molding method, an inflation molding method, a blow molding method, etc. Among these, the extrusion molding method is preferred from the viewpoint of obtaining a film having excellent transparency, improved toughness, excellent handling properties, and an excellent balance between toughness, surface hardness, and rigidity. The temperature of the molten resin discharged from the extruder is preferably set to 160 to 270°C, more preferably 220 to 260°C.
[0107] Among the extrusion molding methods, the T-die method is preferred from the viewpoint of obtaining a film with good surface smoothness, good mirror gloss, and low haze. In this T-die method, it is preferable to sandwich the molten resin discharged from the T-die through an extruder, a gear pump, a polymer filter, and a mixer between two or more mirror-finished rolls or mirror-finished belts to form a film. When sandwiching between the mirror-finished rolls or mirror-finished belts, a bank may or may not be formed. The die has an automatic lip opening adjustment function, and the air gap is preferably 100 mm or less. The mirror-finished roll or mirror-finished belt is preferably made of metal. As the mirror-finished roll, a metal rigid roll, a metal elastic roll, etc. can be used, and it is preferable to use a combination of a metal elastic roll and a metal rigid roll. In addition, the surface temperatures of both the mirror-finished roll or the mirror-finished belt are preferably 130°C or less. In addition, it is preferable that at least one of the pair of mirror-finished rolls or mirror-finished belts has a surface temperature of 60°C or more. By setting the surface temperature at such a level, the molten resin discharged from the extruder can be cooled at a rate faster than natural cooling, and a film with excellent surface smoothness and low haze can be easily produced. The linear pressure between the pair of rolls or belts is preferably 10 N / mm or more, more preferably 30 N / mm or more. The thickness of the unstretched film obtained by extrusion molding is preferably 10 to 300 μm. The haze of the film at a thickness of 100 μm is preferably 0.7% or less, more preferably 0.5% or less, and even more preferably 0.3% or less.
[0108] The unstretched film obtained as described above may be subjected to a stretching treatment. The stretching treatment increases the mechanical strength, and a film that is less likely to crack can be obtained. The stretching method is not particularly limited, and examples thereof include simultaneous biaxial stretching, sequential biaxial stretching, and tubular stretching. From the viewpoint of obtaining a film that can be uniformly stretched and has high strength, the lower limit of the temperature during stretching is a temperature 10°C higher than the glass transition temperature of the methacrylic copolymer or methacrylic copolymer composition, and the upper limit of the temperature during stretching is a temperature 40°C higher than the glass transition temperature of the methacrylic copolymer or methacrylic copolymer composition. The stretching is usually performed at 100 to 5000% / min. After stretching, a film with little thermal shrinkage can be obtained by heat setting. The thickness of the film after stretching is preferably 10 to 200 μm.
[0109] A functional layer may be provided on the surface of the film, which is one embodiment of the molded article of the present invention. Examples of the functional layer include a hard coat layer, an antiglare layer, an antireflection layer, an antisticking layer, a diffusion layer, an antiglare layer, an antistatic layer, an antifouling layer, and a slippery layer such as a fine particle layer.
[0110] In addition, it is preferable to provide an undercoat layer on at least one side of the film of the present invention in order to improve the adhesive strength with the functional layer or to improve the adhesive strength when laminated with other films via an adhesive or pressure-sensitive adhesive.
[0111] The undercoat layer may be made of any of the following resin components: polyester resin, acrylic resin, urethane resin, cellulose resin, polyol resin, polycarboxylic acid resin, cellulose derivative resin, polyvinyl butyral resin, and any composite resin thereof. These resins and composite resins may be modified with hydrophilic groups such as hydroxyl groups, amino groups, isocyanate groups, and carboxy groups. From the viewpoint of durability, it is preferable to blend a crosslinking agent having a reactive group such as an isocyanate group, an epoxy group, a silanol group, a hydrazide group, a carbodiimide group, an oxazoline group, an acetoacetyl group, or an aziridine group with these resins. As the solvent, known solvents such as water; alcohols such as propanol, isopropanol, butanol, and 3-methyl-3-methoxy-1-butanol; aromatic hydrocarbons such as toluene and xylene; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and ethylene glycol esters such as methoxyethanol and ethoxyethanol can be used. To form the undercoat layer, known coating methods such as microgravure and bar coating can be used. When forming the undercoat layer, the drying temperature and time are extremely important, and it is preferable to dry at a temperature of usually 80° C. or higher, preferably 85° C. or higher, more preferably 90° C. or higher, and further preferably 95° C. or higher. Furthermore, it is preferable to carry out a heat treatment in order to complete the crosslinking reaction.
[0112] A laminate can be obtained by laminating a layer containing the methacrylic copolymer or methacrylic copolymer composition of the present invention with other materials (e.g., a layer containing other thermoplastic copolymers). Examples of other materials used in the laminate include steel, plastics (e.g., other thermoplastic resins), wood, glass, etc. The laminate obtained by the present invention can be suitably used for wallpaper; automobile interior surface; automobile exterior surface such as bumpers; mobile phone surface; furniture surface; personal computer surface; vending machine surface; bathroom surface such as bathtub, etc. Examples of other thermoplastic resins that may be used in the layer containing another thermoplastic copolymer include olefin-based resins such as methacrylic resin, polycarbonate, polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene-based ionomers; styrene-based resins such as polystyrene, styrene-maleic anhydride copolymer, high impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate-styrene copolymer; polyethylene terephthalate; and polybutylene terephthalate; amide resins such as nylon 6, nylon 66, and polyamide elastomer; polyphenylene sulfide, polyether ether ketone, polysulfone, polyphenylene oxide, polyimide, polyetherimide, polyvinyl chloride, polyvinylidene chloride, polyvinylidene fluoride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyacetal, and phenoxy resins, among which methacrylic resin and polycarbonate are preferred, and polycarbonate is more preferred.
[0113] The laminate, which is one embodiment of the laminate, is composed of a layer containing the methacrylic copolymer or methacrylic copolymer composition of the present invention and a layer containing a polycarbonate resin, and is highly transparent and has little warping under high temperature and high humidity, making it suitable for optical applications, and is particularly suitable for use as a liquid crystal protection plate, a surface material for a portable information terminal, a display window protection plate for a portable information terminal, and a front plate for various displays.The laminate of the present invention has high transparency and heat resistance, so it can be used for applications other than optical applications, such as decorative sheets, metal decorative sheets, vehicle glazing, machine tool covers, crime prevention sheets, and shatterproof sheets.
[0114] When a laminate comprising a layer containing the methacrylic copolymer or methacrylic copolymer composition of the present invention and a layer containing a polycarbonate resin, which is one form of the laminate, is used for the front panel of various displays, the layer containing the methacrylic copolymer composition of the present invention may be laminated on only one side of the layer containing the polycarbonate resin, or may be laminated on both sides. The thickness of the layer containing the methacrylic copolymer composition is preferably in the range of 2 to 15%, more preferably in the range of 3 to 12%, and even more preferably in the range of 4 to 10% of the thickness of the laminate.
[0115] The methacrylic copolymer, methacrylic copolymer composition, or methacrylic copolymer composition of the present invention is suitable as a molding material. The molded article of the present invention can be used as a member for various applications. Specific applications include, for example, signboard parts and marking films such as advertising towers, stand signs, side signs, transom signs, and rooftop signs; display parts such as showcases, partitions, and store displays; lighting parts such as fluorescent light covers, mood lighting covers, lampshades, light ceilings, light walls, and chandeliers; interior parts such as furniture, pendants, and mirrors; architectural parts such as doors, domes, safety window glass, partitions, staircase wainscoting, balcony wainscoting, and roofs of leisure buildings; transportation-related parts such as aircraft windshields, pilot visors, motorcycle and motorboat windshields, bus shading plates, automobile side visors, rear visors, head wings, headlight covers, automobile interior parts, and automobile exterior parts such as bumpers; audiovisual nameplates, stereo covers, tapes, etc. Examples of applications include electronic equipment parts such as Levi's protective masks, vending machines, mobile phones, and personal computers; medical equipment parts such as incubators and X-ray parts; equipment-related parts such as machine covers, instrument covers, experimental equipment, rulers, dials, and observation windows; optical parts such as liquid crystal protection plates, light guide plates, light guide films, Fresnel lenses, lenticular lenses, front panels of various displays, and diffusion plates; traffic-related parts such as road signs, information boards, curved mirrors, and soundproof walls; and other parts for greenhouses, large aquariums, box aquariums, bathroom components, clock panels, bathtubs, sanitary products, desk mats, game parts, toys, musical instruments, face protection masks during welding, back sheets for solar cells, front sheets for flexible solar cells, and decorative films.
[0116] The laminate obtained by the present invention can be suitably used for wallpaper, surfaces of automobile interior parts, surfaces of automobile exterior parts such as bumpers, surfaces of mobile phones, surfaces of furniture, surfaces of personal computers, surfaces of vending machines, surfaces of bathroom parts such as bathtubs, etc.
[0117] The film, which is one embodiment of the molded article of the present invention, is highly transparent and heat resistant, and therefore suitable for optical applications, and is particularly suitable for polarizer protection films, liquid crystal protection plates, surface materials for portable information terminals, display window protection films for portable information terminals, light guiding films, transparent conductive films with silver nanowires or carbon nanotubes applied to the surface, and front panels for various displays. The film of the present invention has high transparency and heat resistance, and can be used for applications other than optical applications, such as infrared cut films, crime prevention films, shatterproof films, decorative films, metal decorative films, shrink films, and in-mold label films.
[0118] When the film, which is one embodiment of the molded article of the present invention, is used as a polarizer protective film or a retardation film, it may be laminated on only one side of the polarizer film or on both sides. When laminating with the polarizer film, it can be laminated via an adhesive layer or a pressure-sensitive adhesive layer. As the polarizer film, a stretched film made of a polyvinyl alcohol resin and iodine can be used, and its thickness is preferably 1 to 100 μm. EXAMPLES
[0119] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0120] Measurements of physical properties were carried out by the following methods.
[0121] (Weight average molecular weight Mw, molecular weight distribution Mw / Mn) The weight average molecular weight of the resin obtained in the manufacturing example was determined by the GPC method (gel permeation chromatography method). 4 mg of the resin to be measured was dissolved in 5 ml of tetrahydrofuran to prepare a sample solution. The temperature of the column oven was set to 40°C, and 20 μl of the sample solution was injected into the device at an eluent flow rate of 0.35 ml / min to measure the chromatogram. Ten standard polystyrene points with molecular weights in the range of 400 to 5,000,000 were measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight was created. The Mw of the resin to be measured was determined based on this calibration curve. The value corresponding to the molecular weight of the standard polystyrene from the chromatogram measured by GPC was taken as the molecular weight of the copolymer. Equipment: Tosoh GPC equipment HLC-8320 Separation column: Tosoh Corporation's TSKguardcolum SuperHZ-H, TSKgel HZM-M, and TSKgel SuperHZ4000 connected in series Eluent: Tetrahydrofuran Eluent flow rate: 0.35 ml / min Column temperature: 40℃ Detection method: Refractive index (RI)
[0122] (Polymerization conversion rate) A gas chromatograph GC-14A manufactured by Shimadzu Corporation was connected to an INERTCAP1 (df=0.4 μm, 0.25 mm I.D.×60 m) manufactured by GL Sciences Inc. as a column, and analysis was performed under the following conditions, and calculations were made based on the results. injection temperature=250℃ detector temperature=250℃ Temperature conditions: Hold at 60°C for 5 minutes → Raise temperature to 250°C at 10°C / min → Hold at 250°C for 10 minutes
[0123] (Composition of each unit in the copolymer) 1 The proton ratio of the phenyl group of the α-methylstyrene unit and the methoxy group of the methyl methacrylate unit was determined by H-NMR, and the α-methylstyrene unit was calculated based on this.
[0124] (glass transition temperature Tg) The methacrylic copolymers obtained in the Production Examples, Examples, and Comparative Examples were heated once to 250° C., then cooled to room temperature, and the DSC curves were measured in accordance with JIS K7121 using a differential scanning calorimeter (Shimadzu Corporation, DSC-50 (product number)) under conditions of heating from room temperature to 200° C. at a rate of 10° C. / min. The midpoint glass transition temperature determined from the DSC curve measured during the second heating was taken as the glass transition temperature in the present invention.
[0125] (Imidization rate) 1 The copolymer was analyzed using H-NMR (Bruker Corporation; product name: ULTRA SHIELD 400 PLUS). 1 H-NMR measurement was performed, and the O-CH 3 The area A of the peak due to the N-CH group of glutarimide at around 3.0 to 3.3 ppm 3 The value calculated from the area B of the peak derived from the group using the following formula was taken as the imidization rate (mol %). (Imidization rate (mol%)) = B / (A+B) x 100 The imidization rate (wt%) was calculated from the imidization rate (mol%).
[0126] (Acid value) 0.3g of polymer sample was dissolved in a mixed solvent of 37.5ml of dichloromethane and 37.5ml of methanol. Two drops of phenolphthalein ethanol solution were added to the solution, followed by 5ml of 0.1N sodium hydroxide solution. 0.1N hydrochloric acid was added dropwise to the solution until it was neutralized, and the difference between the amount of hydrochloric acid used and the amount of base added until neutralization was reached was calculated in milliequivalents to obtain the acid value.
[0127] (1% thermogravimetric reduction temperature) The methacrylic copolymer or the resin obtained in the production example was heated at 10°C / min in a nitrogen atmosphere using a thermogravimetric analyzer (Shimadzu Corporation, TGA-50), and the temperature at which the weight was reduced by 1% was recorded as the 1% thermal weight loss temperature.
[0128] (3-point bending modulus) The methacrylic copolymer was press-molded into a 4.0 mm sheet. A test piece of 10 mm x 80 mm was cut out from the center of the press-molded sheet. Measurements were performed on a 4 mm thick test piece in accordance with JIS K7171.
[0129] (Hayes) The methacrylic copolymer was press-molded into a sheet of 3.0 mm thickness. The haze of the press plate was measured using a haze meter (manufactured by Murakami Color Research Laboratory; product name HM-150) in accordance with JIS K7136.
[0130] (Total light transmittance) The total light transmittance of the above-mentioned pressed plate (3 mm) was measured using a haze meter (manufactured by Murakami Color Research Laboratory; product name HM-150) in accordance with JIS K7361-1. (transparency) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the methacrylic copolymer compositions obtained in the Examples and Comparative Examples were injection molded under conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain square injection-molded pieces with a thickness of 3 mm and a side length of 50 mm. The total light transmittance (Tt) of the obtained injection molded piece was measured in accordance with JIS K7361-1, and the following evaluations were made based on the obtained Tt. ◎: Tt is 90% or more ○: Tt is 85% or more and less than 90% ×: Tt is less than 85%
[0131] (Vicat softening point temperature; VST) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the methacrylic copolymer compositions obtained in the examples and comparative examples were injection molded under the conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain rectangular test pieces having a thickness of 4 mm, a long side of 80 mm, and a short side of 10 mm. The Vicat softening temperature (VST) of each test piece was measured using an HDT tester 3M-2 manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with the method described in the B50 method of JIS K7206.
[0132] (saturated water absorption rate) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the methacrylic copolymer obtained in the manufacturing example and the methacrylic copolymer composition obtained in the examples and comparative examples were injection molded under the conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain a square test piece having a thickness of 3 mm and a side length of 50 mm. The test piece was vacuum dried for 24 hours under conditions of a temperature of 80°C and 5 mmHg. The test piece was then allowed to cool in a desiccator. The test piece was taken out of the desiccator and the mass (initial mass) was measured immediately. The test piece was then immersed in distilled water at 23°C. The test piece was taken out of the water, the water adhering to the surface was wiped off, and the mass was measured. Immersion in distilled water and mass measurement were repeated until there was no change in mass. The saturated water absorption rate was calculated from the mass (absorbed mass) when there was no change in mass and the initial mass by the following formula. Saturated water absorption rate (%) = [(absorbed mass - initial mass) / initial mass] × 100] (Melt Flow Rate; MFR) The resins obtained in the Production Examples, Examples and Comparative Examples were measured in accordance with JIS K7210 under conditions of 230° C., 3.8 kg load and 10 minutes.
[0133] (Surface hardness) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the methacrylic copolymer compositions obtained in the Examples and Comparative Examples were injection molded under conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain square injection-molded pieces with a thickness of 3 mm and a side length of 50 mm. In addition, the methacrylic copolymer composition and polycarbonate obtained in the examples and comparative examples were continuously fed into a single screw extruder, and the molten methacrylic copolymer composition and polycarbonate were introduced into a junction block, laminated in a multi-manifold die set at 250°C, and extruded into a sheet to obtain a laminated sheet having a thickness of 1000 μm, which is formed from two layers, a layer (80 μm) made of the methacrylic copolymer composition and a layer (920 μm) made of polycarbonate. The laminated sheet was cut into a rectangle with the long side parallel to the extrusion flow direction and the short side perpendicular to the extrusion flow direction, to prepare an extrusion test piece with a long side of 200 mm and a short side of 120 mm. Using a moving table pencil scratch tester (Model P) (manufactured by Toyo Seiki Co., Ltd.), the presence or absence of scratches was confirmed while pressing a pencil lead against one side of the injection molded piece and the surface of the methacrylic copolymer composition side of the extrusion test piece at an angle of 45 degrees and a load of 750 g. The hardness of the pencil lead was gradually increased, and the hardness of the lead one level softer than the point at which the scratch occurred was taken as the pencil scratch hardness. ◎: The pencil hardness of both the injection and extrusion test pieces is 3H or higher. ○: The pencil hardness of both the injection and extrusion test pieces is 2H ×: The pencil hardness of the injection or extrusion test piece is H or less.
[0134] (Moldability) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the methacrylic copolymer compositions obtained in the Examples and Comparative Examples were injection molded under the conditions of a cylinder temperature of 280°C, a mold temperature of 75°C, and a molding cycle of 1 minute to produce flat plates with a length of 205 mm, a width of 160 mm, and a thickness of 0.5 mm. The ratio of the resin flow length (190 mm) to the thickness was 380. In addition, the methacrylic copolymer composition and polycarbonate obtained in the examples and comparative examples were continuously fed into a single screw extruder, and the molten methacrylic copolymer composition and polycarbonate were introduced into a junction block, laminated in a multi-manifold die set at 250°C, and extruded into a sheet to obtain a laminated sheet having a thickness of 1000 μm, which is formed from two layers, a layer (80 μm) made of the methacrylic copolymer composition and a layer (920 μm) made of polycarbonate. The laminated sheet was cut into a rectangle with the long side parallel to the extrusion flow direction and the short side perpendicular to the extrusion flow direction, to prepare an extrusion test piece with a long side of 200 mm and a short side of 120 mm. The appearance of the flat plate was visually observed. The moldability was judged based on the presence or absence of molding defects such as sink marks due to insufficient fluidity and silver streaks due to insufficient thermal decomposition resistance. The appearance of the laminated sheet was also visually observed. The moldability was judged based on the presence or absence of disturbances (flow patterns) at the laminate interface due to insufficient fluidity and foaming or gel particles due to insufficient thermal decomposition resistance. ◎: No sink marks in the molded product, no silver streaks, no disturbances in the interface of the laminated sheets, and no foaming or gel particles. ○: Slight sink marks or silver streaks in the molded product, or slight disturbance, foaming, or gel particles in the laminated sheet interface. ×: Sink marks or silver streaks were observed in the molded product, or the laminate interface of the laminated sheet was disturbed, foamed, or had gel particles.
[0135] (Dimensional stability) The methacrylic copolymer compositions obtained in the examples and comparative examples were press molded to produce flat plates with a length of 205 mm, a width of 160 mm, and a thickness of 0.5 mm. The flat plates were placed in either (1) an incubator at a temperature of 60°C and a relative humidity of 90%, or (2) a thermostat at a temperature of 90°C and a relative humidity of 60%, and left in the air for 500 hours. The flat plates were removed from the incubator, and the lengthwise dimensions were measured. The dimensional change rate from the lengthwise dimensions before being placed in the incubator was calculated. Under both conditions (1) and (2), samples with a dimensional change rate of 0.3% or less were given an A rating, and all other samples were given a B rating. A: The dimensional change rate of the molded product is 0.3% or less B: The dimensional change rate of the molded product is greater than 0.3% In addition, the laminated sheet test piece was placed on a surface plate so that both ends of the test piece were in contact with the surface plate (i.e., the test piece was in an upward convex shape), and the maximum gap between the test piece and the surface plate was measured using a gap gauge, which was taken as the initial warpage. Next, each test piece was left in a hot air dryer set at a temperature of 100°C for 1 hour, and then the test piece, with its short side secured by a clip, was hung in an environmental tester set at a temperature of 85°C and a relative humidity of 85%, and left in that state for 72 hours, and then allowed to cool and humidify for 120 hours under an environment of 23°C and a relative humidity of 50%. As a result, all test pieces were warped in a bow shape along the long side of the test piece, with the layer made of the methacrylic copolymer composition on the outside and the layer made of polycarbonate on the inside. The test piece with such bow warpage was placed on a surface plate so that both ends of the test piece were in contact with the surface plate (i.e., the test piece was in an upward convex shape), and the maximum gap between the test piece and the surface plate was measured using a gap gauge, which was taken as the warpage under high temperature and high humidity. The amount of warpage change under high temperature and high humidity was calculated using the formula below. Those with a warpage change of 4 mm or less under high temperature and high humidity were given an A rating, and those with a warpage change of more than 4 mm were given a B rating. Warpage change under high temperature and humidity = Warpage under high temperature and humidity - Initial warpage A: Warpage change under high temperature and humidity is 4 mm or less B: Warpage change under high temperature and humidity is greater than 4 mm The dimensional stability was judged based on the evaluation results of the press-molded flat plate and the laminated sheet. ◎: Both press-molded flat plates and laminated sheets were rated A ○: Press-molded flat plate or laminated sheet is rated A ×: The press-molded flat plate and laminated sheet were rated B.
[0136] <Examples of various materials> For the methacrylic resin (B) according to the present invention, the following materials were used. Methacrylic resin (B-1): Parapet made by Kuraray Co., Ltd. (Mw=64,000, rr ratio=49%, MMA copolymerization ratio=95.5%, MA copolymerization ratio=4.5%, Tg=112℃, saturated water absorption rate=2.0%) Methacrylic resin (B-2): Parapet made by Kuraray Co., Ltd. (Mw=80,000, rr ratio=52%, MMA copolymerization ratio=100%, MA copolymerization ratio=0%, Tg=119℃, saturated water absorption rate=2.0%) Methacrylic resin (B-3): Parapet made by Kuraray Co., Ltd. (Mw=69,000, rr ratio=74%, MMA copolymerization ratio=100%, MA copolymerization ratio=0%, Tg=130℃, saturated water absorption rate=2.0%) Methacrylic resin (B-4): Parapet made by Kuraray Co., Ltd. (Mw=78,000, rr ratio=45%, MMA copolymerization ratio=88.7%, MA copolymerization ratio=11.3%, Tg=101℃, saturated water absorption rate=2.0%)
[0137] Manufacturing Examples 1 to 5 Purified methyl methacrylate (MMA), methyl acrylate (MA), 2,2'-azobis(2-methylpropionitrile) (AIBN) and n-octyl mercaptan (n-OM) were charged in the ratios shown in Table 1 into autoclave A equipped with a stirrer and dissolved uniformly to obtain polymerization raw materials. The polymerization raw materials were continuously supplied from autoclave A at 1.5 kg / hr to a tank reactor controlled at the polymerization temperature shown in Table 1, and polymerization reaction was carried out by bulk polymerization at the average residence time shown in Table 1, and a liquid containing a methacrylic copolymer was continuously discharged from the tank reactor. The polymerization conversion rate was the value shown in Table 1. Next, the liquid discharged from the reactor was heated to 230°C and supplied to a twin-screw extruder controlled at 240°C. In the twin-screw extruder, volatile matters mainly composed of unreacted monomers were separated and removed, and the methacrylic copolymers (precursor polymers Aa to Ae in Table 1) were extruded into strands. The strands were cut with a pelletizer to obtain copolymer pellets.
[0138] The copolymer pellets were used to measure the weight average molecular weight Mw, molecular weight distribution Mw / Mn, the proportion of α-methylstyrene units, the glass transition temperature Tg, and MFR. The results are shown in Table 1.
[0139] Production Example 6 According to the method for producing copolymer (A) described in the section [Examples] of JP 2003-231785 A, MS resin (copolymer of methyl methacrylate (MMA) and styrene (St)) was polymerized. The mass ratio of MMA and St charged into the autoclave was changed to obtain precursor polymer (Af). Precursor polymer (Af) has the following physical properties. MMA unit content: 90wt% α-MS unit content: 0wt% St unit content: 10wt% Weight average molecular weight (MW): 95000 Glass transition temperature: 116℃ MFR (230℃, 3.8kg): 3.7g / 10min.
[0140] [Table 1]
[0141] Example 1 The precursor polymer [Aa] was fed at 2 kg / hr to the transport section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600) consisting of a transport section, a melt-kneading section, a devolatilizing section, and a discharge section, and the screw speed and temperature were set at 120 rpm and 250° C., respectively, and monomethylamine was injected at 0.10 kg / hr from the additive supply port of the twin-screw extruder in the melt-kneading section equipped with a kneading block, to react the precursor polymer [Aa] with monomethylamine. A reverse flight was installed on the screw at the end of the reaction zone. In the volatilizing section set at 20 Torr (about 2.7 kPa), by-products and excess monomethylamine were volatilized from the molten resin that had passed through the melt-kneading section, and discharged through a vent. The molten resin extruded as a strand from a die provided at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped methacrylic copolymer (Aa-1).
[0142] A twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600) consisting of a transport section, a melt-kneading section, a devolatilizing section and a discharge section, was set at a screw speed of 100 rpm and a temperature of 230 ° C. The methacrylic copolymer (Aa-1) was fed at 1 kg / hr to the transport section, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.024 kg / hr in the melt-kneading section in which a kneading block was installed, and the dimethyl carbonate was reacted with the acidic components (carboxyl groups and acid anhydrides) remaining in the methacrylic copolymer (Aa-1). A reverse flight was installed on the screw at the end of the reaction zone. In the volatilizing section set at 20 Torr (about 2.7 kPa), by-products and excess dimethyl carbonate were volatilized from the molten resin that had passed through the melt-kneading section, and were discharged through a vent. The molten resin extruded as a strand from a die provided at the end of the discharge part of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped methacrylic copolymer (Aa-2).
[0143] The methacrylic copolymer (Aa-2) was supplied at 1 kg / hr to the transport section of a twin-screw extruder (manufactured by Technobel Co., Ltd.; product name KZW20TW-45MG-NH-600), which consisted of a transport section, a melt-kneading section, a devolatilization section, and a discharge section, and was set at a screw rotation speed of 100 rpm and a temperature of 230°C. In the volatilizing section set at 20 Torr (approximately 2.7 kPa), volatile matters such as unreacted substances were volatilized from the molten resin that had passed through the melt-kneading section, and discharged through a vent. The molten resin extruded as a strand from a die installed at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain a pellet-shaped methacrylic copolymer (A-1, imidized polymer in Table 2). The methacrylic copolymer (A-1) had an imidization rate (proportion of structural unit (R)) of 14.3 wt%. The methyl methacrylate unit of the methacrylic copolymer (A-1) was {(100-8)-2×14.3}=63.4 wt%. The physical properties of the methacrylic copolymer (A-1) are shown in Table 2.
[0144] Example 2 A methacrylic copolymer (A-2) was obtained in the same manner as in Production Example 1, except that the precursor polymer [Ab] was used instead of the precursor polymer [Aa], the amount of monomethylamine added was 0.07 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.018 kg / hr. The physical properties of the methacrylic copolymer (A-2) are shown in Table 2.
[0145] Example 3 A methacrylic copolymer (A-3) was obtained in the same manner as in Production Example 1, except that the precursor polymer [Ab] was used instead of the precursor polymer [Aa], the amount of monomethylamine added was 0.14 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.036 kg / hr. The physical properties of the methacrylic copolymer (A-3) are shown in Table 2.
[0146] Example 4 A methacrylic copolymer (A-4) was obtained in the same manner as in Production Example 1, except that the precursor polymer [Ac] was used instead of the precursor polymer [Aa], the amount of monomethylamine added was 0.07 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.018 kg / hr. The physical properties of the methacrylic copolymer (A-4) are shown in Table 2.
[0147] Comparative Example 1 A methacrylic copolymer (A-5) was obtained in the same manner as in Production Example 1, except that the precursor polymer [Ad] was used instead of the precursor polymer [Aa], the amount of monomethylamine added was 0.03 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.008 kg / hr. The physical properties of the methacrylic copolymer (A-5) are shown in Table 2.
[0148] Comparative Example 2 A methacrylic copolymer (A-6) was obtained in the same manner as in Example 1, except that the amount of monomethylamine added was 0.30 kg / hr and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.075 kg / hr. The physical properties of the methacrylic copolymer (A-6) are shown in Table 2.
[0149] Comparative Example 3 A methacrylic copolymer (A-7) was obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ae), the amount of monomethylamine added was 0.07 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.018 kg / hr. The physical properties of the methacrylic copolymer (A-7) are shown in Table 2.
[0150] Comparative Example 4 A methacrylic copolymer (A-8) was obtained in the same manner as in Production Example 1, except that the precursor polymer (Aa) was replaced by the precursor polymer (Ae), the amount of monomethylamine added was 0.45 kg / hr, and a liquid consisting of 0.8 parts by mass of dimethyl carbonate and 0.2 parts by mass of triethylamine was injected at 0.125 kg / hr. The physical properties of the methacrylic copolymer (A-8) are shown in Table 2.
[0151] Comparative Example 5 A methacrylic copolymer (A-9) was obtained in the same manner as in Production Example 1, except that the precursor polymer (Ab) was used instead of the precursor polymer (Aa), no additives were added, and the mixture was passed through the extruder. The physical properties of the methacrylic copolymer (A-9) are shown in Table 2. Comparative Example 6 Except for using the precursor polymer [Af] instead of the precursor polymer [Aa], a methacrylic copolymer (A-10) was obtained in the same manner as in Example 1. The physical properties of the methacrylic copolymer (A-10) are shown in Table 2.
[0152] [Table 2]
[0153] The methacrylic copolymers obtained in Examples 1 to 4 have high heat resistance, low saturated water absorption, good thermal decomposition resistance, high transparency, and high elasticity, and are therefore suitable for optical components such as polarizing plate protective films. On the other hand, the methacrylic copolymers obtained in Comparative Examples 1 to 6 are not within the scope of the present invention, and therefore are inferior to the present invention in any of the following aspects: low heat resistance, low saturated water absorption, or poor thermal decomposition resistance.
[0154] Example 5 80 parts by mass of methacrylic copolymer (A-1) and 20 parts by mass of methacrylic resin (B-1) were mixed, melt-kneaded at 250°C in a twin-screw extruder with a shaft diameter of 20 mm, and extruded to obtain a methacrylic copolymer composition (C-1). The evaluation results are shown in Table 3.
[0155] Examples 6 to 11 Methacrylic copolymer compositions (C-2) to (C-7) were obtained in the same manner as in Example 5 except for the formulations shown in Table 3. The evaluation results are shown in Table 3.
[0156] Comparative Examples 7 to 14 Methacrylic copolymer compositions (C-8) to (C-15) were obtained in the same manner as in Example 5 except for the formulations shown in Table 4. The evaluation results are shown in Table 4.
[0157] [Table 3]
[0158] [Table 4]
[0159] As shown in Tables 3 and 4, the methacrylic copolymer composition of the present invention contains a methacrylic copolymer having an excellent balance of heat resistance, low water absorption, and thermal decomposition resistance, and therefore has excellent appearance quality without foaming and excellent dimensional stability. Furthermore, since the methacrylic copolymer of the present invention has the characteristic of having excellent compatibility with methacrylic resins, the methacrylic copolymer composition of the present invention retains transparency even when a methacrylic resin is added, and has excellent flowability. The methacrylic copolymer composition of the present invention can provide molded products and laminates having excellent dimensional stability, moldability, and surface hardness. [Industrial Applicability]
[0160] The laminate of the present invention has excellent appearance quality and is characterized by good dimensional stability and surface hardness, and is suitable for use as covers and housings for display devices, window materials and covers for the interior and exterior of vehicles, and the like.
Claims
1. It contains 40 to 87% by mass of methyl methacrylate units, 6 to 30% by mass of structural units (R) which are N-substituted glutarimide units represented by formula (1), and 7 to 30% by mass of α-methylstyrene units, A methacrylic copolymer having a glass transition temperature of 130°C or higher. 【Chemistry 1】 (In formula (1), R 1 is each independently a hydrogen atom or a methyl group, and R 2 is an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.)
2. The methacrylic copolymer according to claim 1, having a saturated water absorption of 2.5% or less.
3. A methacrylic copolymer composition comprising the copolymer according to claim 1 or 2.
4. The methacrylic copolymer composition according to claim 3, further comprising at least one selected from the group consisting of antioxidants and ultraviolet absorbers.
5. The methacrylic copolymer composition according to claim 3, comprising 51 to 99 mass% of a methacrylic copolymer (A) which contains 40 to 87 mass% of methyl methacrylate units, 6 to 30 mass% of structural units (R) which are N-substituted glutarimide units represented by formula (1), and 7 to 30 mass% of α-methylstyrene units and has a glass transition temperature of 130° C. or higher, and 1 to 49 mass% of a methacrylic resin (B). 【Chemistry 2】 (In formula (1), R 1 is each independently a hydrogen atom or a methyl group, and R 2 is an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.)
6. The methacrylic copolymer composition according to claim 5, having a glass transition temperature of 120°C or higher.
7. The methacrylic copolymer composition according to claim 5 or 6, which has a saturated water absorption of 2.5% or less.
8. The methacrylic copolymer composition according to any one of claims 5 to 7, wherein the melt flow rate of a molded product measured at 230°C under a load of 3.8 kg according to the method specified in JIS K7210 is 1.0 g / 10 min or more.
9. A molded article comprising the methacrylic copolymer according to claim 1 or 2, or the methacrylic copolymer composition according to any one of claims 3 to 8.
10. A film comprising the methacrylic copolymer according to claim 1 or 2, or the methacrylic copolymer composition according to any one of claims 3 to 8.
11. A laminate having a layer containing the methacrylic copolymer according to claim 1 or 2 or the methacrylic copolymer composition according to any one of claims 3 to 8, and a layer containing another material.
12. A step of continuously supplying a reaction raw material including a monomer mixture containing 70 to 93 mass % of methyl methacrylate, 30 to 7 mass % of α-methylstyrene, and 0 to 10 mass % of a copolymerizable monomer, and a radical polymerization initiator, to a tank-type reactor; A step of bulk polymerizing the monomer mixture in a tank reactor to a polymerization conversion rate of 30 to 60 mass % to obtain a reaction product; and removing the monomer mixture in the reaction product; The method for producing the methacrylic copolymer according to claim 1 or 2, further comprising a step of subjecting the obtained precursor polymer to a ring structure-forming reaction.
Citation Information
Patent Citations
JP1968026187B
Optical disk substrate
JP1988163302A
Optical isotropic protective film for polarizing film, and polarizing plate
JP2013033237A
Methacrylic resin, methacrylic resin composition, film, and production methods
JP2017101225A
Process for copolymerizing alpha-methyl styrene and methyl methacrylate
US3135723A